Energy and Emissions Conflicts in Urban Areas - Touria Abdelkader B. Conde; Fernando Barreiro-Pereira (European Regional Science Association (ERSA), 2014)
The main aim of this paper is to observe the environmental behaviour in some cities of the word, by analyzing for each city the trends of several energy and emissions indicators that appear as explanatory variables in both energy and labour average productivity equations. At the same time we also consider the life expectancy at birth as an endogenous variable which be partially explained by these indicators to for observing the carbon dioxide (CO2) effects on the population health. To quantify how affect changes in carbon dioxide emissions, energy production and consumption on the some countries life expectancy, climate change, and labour and energy productivities, we used panel data techniques across some metropolitan areas with IEA annual data. Following the results concerning to the proposed indicators, the energy consumption per inhabitant and CO2 emissions by Km2 are highest around the oil producer countries like Qatar, Emirates and Kuwait, and among the High-Tech user countries like China, Japan, South Korea and Singapore. The more high energy productivity is in Japan, Singapore and Turkey. Only carbon dioxide emissions are addressed in this paper, but it does not address other emmissions such as NOx or SOx. In other hand, we assume by simplicity perfect competition in the good markets to can calculate an energy price indicator for the renewable and non-renewable energies in each city. The paper relates issues to central questions of international politics and theoretical debates concerning to the levels of consumption per head, carbon dioxide emissions/surface and the role of the renewable energies on the climate change and the wellbeing of the consumers. We classify the cities in Oil producers, Coal producers, High-Tech users, and Poor cities. Assumming perfect rationality in the energy producers, we can calculate the costs for change the use of fossil energies by renewable energies.
Keywords: Q01; Q42; Q47; Q53; 330; Emissions; Renewable Energy; Cities; Economic Conflicts; Political Conflicts